Stressful life experiences and risk of relapse of breast cancer: observational cohort study. Issue 7351 (15th June 2002) - Graham, Jill; Ramirez, Amanda; Love, Sharon; Richards, Michael; Burgess, Caroline
Abstract: Objective: To confirm, using an observational cohort design, the relation between severely stressful life experiences and relapse of breast cancer found in a previous case-control study. Design: Prospective follow up for five years of a cohort of women newly diagnosed as having breast cancer, collecting data on stressful life experiences, depression, and biological prognostic factors. Setting: NHS breast clinic, London; 1991-9. Participants: A consecutive series of women aged under 60 newly diagnosed as having a primary operable breast tumour. 202/222 (91%) eligible women participated in the first life experiences interview. 170 (77%) provided complete interview data either up to 5 years after diagnosis or to recurrence. Main outcome measure: Recurrence of disease. Results: We controlled for biological prognostic factors (lymph node infiltration and tumour histology), and found no increased risk of recurrence in women who had had one or more severely stressful life experiences in the year before diagnosis compared with women who did not (hazard ratio 1.01, 95% confidence interval 0.58 to 1.74, P=0.99). Women who had had one or more severely stressful life experiences in the 5 years after diagnosis had a lower risk of recurrence (0.52, 0.29 to 0.95, P=0.03) than those who did not. Conclusion: These data do not confirm an earlier finding from a case-control study that severely stressful life experiences increase the risk of recurrence of breast cancer. Differences in case control and prospective methods may explain the contradictory results. We took the prospective study as the more robust, and the results suggest that women with breast cancer need not fear that stressful experiences will precipitate the return of their disease.